Pelatihan Digipreneurship pada Santri Pondok Pesantren Tahfidz Al-Qur’an Taqi Boarding School Setu Kabupaten Bekasi - Arfian, Andi; Cahyadi, Cepi; Palasara, Nicodias; Yana, Adelia Alvi; Siregar, Juarmi (Perkumpulan Kualitama Edukatika Indonesia, 2023)
In this modern era, digital literacy or digital insight is very important, especially for pesantren residents who do not yet have digital literacy. Workshop on the importance of digital insights for students at Tahfiz Al-Quran Taqi Boarding School Islamic Boarding School to ensure students are not left behind in the very rapid pace of technological development as well as to learn and equip themselves with the development of the digital economy that is currently growing rapidly. provide students with an understanding of what to do. This workshop is Santri with skills that can be used to create changes that lead to professional management of information and marketing through social media. Overall, the program is running well. Indicators of success can be obtained from the feedback given by the participants while participating in this activity. This means that students have a good understanding of the material presented.